SOME PROBLEMS IN DISTINGUISHING SPECIAL SIMPLE SENTENCES IN VIETNAMESE - Nghi, Trịnh Quỳnh Đông (IJRDO-Journal of Applied Science, 2022)
The existence of special sentences, elliptical sentences, and subsentences is obvious and common in Vietnamese discourse, including all kinds of conversations in daily life, administration, academia, or other types of literature versions of different linguistic functional styles. By surveying many different discourses, through quantitative and qualitative methods, this article points out some problems in understanding the above-mentioned special simple sentences, and at the same time proposes some points to distinguish special sentences, elliptical sentences, and subsentences in order to create favorable conditions for further study of different aspects of these types of sentences.